2020
DOI: 10.1177/1724600819877193
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxin-associated gene A increases carcinogenicity of helicobacter pylori in colorectal adenoma

Abstract: Objective: This study aimed to investigate the correlation of Helicobacter pylori (Hp) infection with disease risk and severity of colorectal adenoma, also to explore the association of cytotoxin-associated gene A (CagA) positive (CagA+)- Hp infection with gastrin and ki-67 expressions in colorectal adenoma patients. Methods: There were 1000 colorectal adenoma patients and 1500 controls consecutively enrolled, then Hp infection status was determined by 14C urea breath test and rapid urease test. Also, serum Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…It is suggested that H. pylori infection is an independent risk factor for colon adenoma, especially in the case of advanced or multiple adenomas. This notion was also demonstrated by the Zhang et al 90 team. The positive rate of H. pylori was higher in patients with CRA than in the control group.…”
Section: Relationship Between Intestinal Metabolites and Colorectal A...supporting
confidence: 58%
“…It is suggested that H. pylori infection is an independent risk factor for colon adenoma, especially in the case of advanced or multiple adenomas. This notion was also demonstrated by the Zhang et al 90 team. The positive rate of H. pylori was higher in patients with CRA than in the control group.…”
Section: Relationship Between Intestinal Metabolites and Colorectal A...supporting
confidence: 58%
“…Measurement of H pylori antibody in our study was conducted using a typing test. The type 1 H pylori produces vacuolating cytotoxin (VacA) and cytotoxin‐associated protein (CagA) and is more infectious and pathogenic than the type 2 H pylori which produces urease subunit A/B (UreA/B) and no cytotoxins 20‐22 …”
Section: Discussionmentioning
confidence: 99%
“…The type 1 H pylori produces vacuolating cytotoxin (VacA) and cytotoxin-associated protein (CagA) and is more infectious and pathogenic than the type 2 H pylori which produces urease subunit A/B (UreA/B) and no cytotoxins. [20][21][22] In the H pylori-infected group, 68.02% were infected with type 1 H pylori, and 31.98% were infected with type 2 H pylori. These data showed that most of the H pylori infection in our region were caused by type 1 H pylori and demonstrated that the type 1 H pylori was more infectious than type 2 H pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is a malignant tumor of the digestive tract that usually occurs in the colon and rectum with high clinical morbidity and fatality rate. As the eating habit of Chinese people has changed in recent years, the incidence of colorectal cancer is on the rise, which seriously affects the physical and mental health and further endangers the life safety of patients (7)(8). HP, as one of the common bacteria for chronic infection, is closely related to several stomach diseases and has a certain correlation with the occurrence of colorectal cancer (9).…”
Section: Discussionmentioning
confidence: 99%